Force-induced optical nonlinearity and Kerr-like coefficient in opto-mechanical ring resonators - Yu, Y. F. (2013)
This paper demonstrates the optical nonlinearity in opto-mechanical ring resonators that consist of a bus waveguide and two ring resonators, which is induced by the optical gradient force and characterized by the Kerr-like coefficient. Each ring resonator has a free-hanging arc that is perpendicularly deformable by an optical gradient force and subsequently this deformation changes the effective refractive index (ERI) of the ring resonator. The change of the ERI induces optical nonlinearity into the system, which is described by an equivalent Kerr coefficient (Kerr-like coefficient). Based on the experimental results, the Kerr-like coefficient of the ring resonator system falls in the range from 7.64 × 10−12 to 2.01 × 10−10 m2W−1, which is at least 6-order higher than the silicon’s Kerr coefficient. The dramatically improved optical nonlinearity in the opto-mechanical ring resonators promises potential applications in low power optical signal processing, modulation and bio-sensing.